An analysis of sepression level of retired professional football players according to their life quality - Bayrak, M.; Tasmektepligil, Y.; Tunc, T.; Aksoy, S. (World Journal of Sport Sciences, 2011)
Abstract: The aim of this study was to determine the life quality and depression levels of retired professional football players and to make an evaluation of their depression levels with respect to life quality. Face-to-face interview method was applied to 388 retired football players and the data were analyzed with SPSS and statistica 7 software in the study. Before the analysis of data, conformity of the score distribution obtained through scales concerning life quality and beck depression levels with the normal distribution was determined by the Shapiro-Wilk's test in order to find the appropriate analysis method. As a result of the test, it was found that the observation values did not display a normal distribution in terms of depression scores whereas it displayed a normal distribution in terms of life quality scores (p<O,05). This study has found out that retired professional football players with higher depression levels have lower life quality levels while those with lower depression levels have higher life quality levels. Significant correlations were seen between demographic variables and sub-dimensions of life quality and depression levels. Nevertheless, no significant correlation was found between depression levels of retired professional football players and their marital status, education level, career in professional leagues and how long they have been retired. As a conclusion, a negative correlation was found between depression scores and life quality scores. In retired professional football players, life quality goes down as depression levels increase, which is attributed to low education level, income, fame/popularity, decreased mobility and marital status.